Innovation and productivity in European industries - Mario Pianta; Andrea Vaona (Kiel Institute for the World Economy (IfW), 2006)
The labour productivity impact of innovation is investigated in this paper combining neo-Schumpeterian insights on the variety of innovation, with the importance of industrial structures and firm size; two models are proposed for explaining productivity and export success in European manufacturing industries and firm size classes. The empirical estimates are based on data from the European innovation survey (CIS 2), covering Austria, France, Italy, the Netherlands and the UK, broken down by 22 sectors and for large, medium and small firms. The econometric results, obtained adopting cross-sectional estimation methodologies able to account for unobserved industrial characteristics, show that productivity in Europe relies on product and process innovation, with the support of the efficiency gains provided by a grouped business structures. Conversely, in Italy the introduction of new machinery linked to innovation appears as the key mechanism supporting domestic productivity. When export success is considered, all countries have to rely on an innovation-based model of competitiveness.
Keywords: O41; O33; O31; 330; Productivity; Export performance; Industries; Innovation; Innovation; Arbeitsproduktivität; Verarbeitendes Gewerbe; Schätzung; Österreich; Frankreich; Italien; Niederlande; Großbritannien; EU-Staaten